1926
DOI: 10.1037/h0073705
|View full text |Cite
|
Sign up to set email alerts
|

Anosmia and its effects upon taste perceptions.

Abstract: Tomato Tomato Cream (choc.) Sweet pickle Sweet pickle Onion Onion Banana Banana (?) Cheese Cheese (?) Date Peanut Nole: In the above table " ?" represents doubt expressed by the subject. The serial order of words represents the order of the subject's judgments.In a few cases substances were missed with one or both controls.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
4
0

Year Published

1929
1929
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(5 citation statements)
references
References 17 publications
1
4
0
Order By: Relevance
“…Such alterations also do not appear after a long term block of the olfactory sensi tivity, chronic anosmia (carp) (Kasumyan and Sidorov, 2005b;. Similar results have also been obtained for humans when com paring congenital anosmia patients and healthy per sons (Gilland, 1921;Crosland et al, 1926;Doty, 1977;Ferris et al, 1985). However, taste preferences alter in the Slc:ICR mice with acute anosmia despite the absence of any changes in the electrophysiological response recorded in the gustatory nerve (chorda tym pani) (Uebayashi et al, 2001).…”
Section: Discussionsupporting
confidence: 56%
“…Such alterations also do not appear after a long term block of the olfactory sensi tivity, chronic anosmia (carp) (Kasumyan and Sidorov, 2005b;. Similar results have also been obtained for humans when com paring congenital anosmia patients and healthy per sons (Gilland, 1921;Crosland et al, 1926;Doty, 1977;Ferris et al, 1985). However, taste preferences alter in the Slc:ICR mice with acute anosmia despite the absence of any changes in the electrophysiological response recorded in the gustatory nerve (chorda tym pani) (Uebayashi et al, 2001).…”
Section: Discussionsupporting
confidence: 56%
“…He reported that he was not able to demonstrate any such compensatory changes due to loss of the sense of smell. Crosland et al (Crosland et al, 1926), using themselves as controls, tested a single anosmic person's ability to taste food. They stated that under blindfold conditions the anosmic person's ability to detect food placed into his mouth did not differ from, or may even have been superior to, that of a person with a sense of smell in the normal range.…”
Section: Eating Behaviourmentioning
confidence: 99%
“…All participants were instructed to repeatedly consume and evaluate the pleasantness of flavor and mouthfeel of different food items. We further hypothesized that any exaggerated SSS among the hyposmic/anosmic participants would be limited to the pleasantness ratings of flavor as olfactory deficit affects flavor perception but not somatosensory perception of food texture (see e.g., Crosland et al 1926Crosland et al , 1928.…”
Section: Introductionmentioning
confidence: 99%